Analyzing the Impact of Problem-based Learning on Mathematical Creativity of Grade 8 High School Students from Pilgrim Christian College - Rosal, John Paul Jay (JPAIR Institutional Research, 2025)
Problem-Based Learning is an approach where students learn concepts and skills by solving complex and real-world problems with emphasis on active engagement, critical thinking, and collaboration. This quasi-experiment investigated the pre-test and post-test scores of the forty-four grade 8 students from Pilgrim Christian College and the impact of problem-based learning to their mathematical creativity. The students belong to two sections, which were the experimental and control group. The researcher used a teacher made test that was validated and an adapted scoring rubrics for mathematical creativity. The statistical techniques that were used includes normality, linear regression, homogeneity of regression slopes and variances. The test was conducted with ANCOVA, however, assumptions failed so Mann-Whitney U test was used. Analyze data shows that the test is statistically significant and mean-ranks indicate that the experimental group have higher post-test scores than the control group, which means that students who were taught using problem-based learning demonstrated higher scores in mathematical creativity than those who received conventional instruction. Therefore, the evidence supports PBL as an effective strategy for nurturing mathematical creativity among grade 8 students from Pilgrim Christian College.